Impact of atrial fibrillation on the risk of major adverse cardiac events following coronary revascularisation. Issue 2 (23rd September 2022) - Jung, Richard G; Abdel-Razek, Omar; Di Santo, Pietro; Gillmore, Taylor; Stotts, Cameron; Makwana, Dwipen; Soriano, Joelle; Moreland, Robert; Verreault-Julien, Louis; Goh, Cheng Yee; Parlow, Simon; Sypkes, Caleb; et al.
Abstract : Objective: Atrial fibrillation (AF) remains a highly prevalent arrhythmia with significant burden on morbidity and mortality. The impact of AF in the revascularised population remains incompletely described. Given the high prevalence of AF in the revascularised population, we sought to evaluate the incidence and prognosis in patients with pre-existing and new-onset AF following revascularisation. Methods: We used the University of Ottawa Heart Institute Revascularisation Registry to identify patients who underwent revascularisation between August 2015 and March 2020, who were prospectively followed for an average of one year. We conducted a retrospective cohort study analysing the association between AF and clinical outcomes. The primary outcome of interest was 1-year major adverse cardiac events (MACE) defined as a composite of death, myocardial infarction, unplanned revascularisation and cerebrovascular accidents. Moreover, secondary outcomes include the individual components of MACE and bleeding. Results: A total of 6704 patients underwent revascularisation and completed 1-year clinical follow-up. Median time to follow-up was 12.8 (IQR 11.2–15.9) months. One-year MACE occurred in 166 (21.8%) and 683 (11.5%) patients in AF and non-AF groups, respectively (adjusted HR, 1.61; 95% CI 1.29 to 2.01; p<0.0001). AF was independently predictive of 1-year mortality, myocardial infarction, unplanned revascularisation, cerebrovascular accident and bleeding. Within 1 year, 299 (4.5%) episodes of new-onset AF was observed. New-onset AF following revascularisation was also associated with 1-year MACE, mortality, myocardial infarction, cerebrovascular accident and unplanned revascularisation. Conclusions: Preprocedural and new-onset AF following revascularisation remains highly predictive 1-year MACE. AF should be considered in addition to traditional risk factors for adverse outcomes following revascularisation.